Labour Market Shocks during the COVID-19 Pandemic, Inequalities and Child Outcomes - Claudia Hupkau; Ingo E. Isphording; Stephen Machin; Jenifer Ruiz-Valenzuela (Institute of Labor Economics (IZA), 2020)
We study the effect of negative labour market shocks borne by parents during the Covid-19 crisis on resource and time investments in children and the channels through which negative labour market shocks experienced by parents might affect children. Using data collected in the UK before and during the pandemic, we show that fathers and mothers that were already disadvantaged were more likely to have suffered negative earnings and employment shocks. These shocks had an immediate intergenerational impact: Children whose fathers reported an earnings drop to zero are significantly less likely to have received additional paid learning resources compared to similar children whose fathers did not experience a drop in earnings. Potentially offsetting this, they received about 30 more mins of parental help with schoolwork per day. Parental mental health is negatively affected when they experience earnings losses, and fathers who experience a full loss in earnings were less likely to quarrel or talk about things that matter with their kids than fathers who did not suffer earnings drops. The interactions between labour market shocks, parental investments and school closures are likely to have important implications for future inequality.
Keywords: J63; J65; I20; I24; 330; job loss; job insecurity; child outcomes